2011
DOI: 10.2337/db10-0940
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Insulin on Brain Glucose Metabolism in Impaired Glucose Tolerance

Abstract: OBJECTIVE-Insulin stimulates brain glucose metabolism, but this effect of insulin is already maximal at fasting concentrations in healthy subjects. It is not known whether insulin is able to stimulate glucose metabolism above fasting concentrations in patients with impaired glucose tolerance.RESEARCH DESIGN AND METHODS-We studied the effects of insulin on brain glucose metabolism and cerebral blood flow in 13 patients with impaired glucose tolerance and nine healthy subjects using positron emission tomography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
103
2
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(126 citation statements)
references
References 25 publications
10
103
2
3
Order By: Relevance
“…The fact that brain insulin may modulate glucose handling by this organ, in concert with brain IGF-I, may explain the difficulty in determining a role for circulating insulin in brain glucose handling. Because diabetes impacts the brain at biochemical, structural, and behavioral levels (6), it is possible that the action of brain insulin may be also altered, unveiling a role for circulating insulin in the diabetic state (2). Furthermore, a role for circulating I+I cannot be entirely ruled out yet, because, at least for the latter, neuronal activity triggers its entrance into the brain (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that brain insulin may modulate glucose handling by this organ, in concert with brain IGF-I, may explain the difficulty in determining a role for circulating insulin in brain glucose handling. Because diabetes impacts the brain at biochemical, structural, and behavioral levels (6), it is possible that the action of brain insulin may be also altered, unveiling a role for circulating insulin in the diabetic state (2). Furthermore, a role for circulating I+I cannot be entirely ruled out yet, because, at least for the latter, neuronal activity triggers its entrance into the brain (19).…”
Section: Discussionmentioning
confidence: 99%
“…Only under pathological circumstances, such as diabetes, do brain glucoregulatory actions of insulin manifest (2). Therefore, mechanisms of neurovascular coupling, whereby active brain regions locally increase glucose and oxygen uptake, are not considered to involve insulin under physiological circumstances.…”
mentioning
confidence: 99%
“…Another study, however, in which a hyperinsulinaemic‐euglycaemic clamp procedure was used, showed that insulin had no effect on CBF when healthy subjects and subjects with impaired glucose tolerance were compared 58. Van Golen et al.…”
Section: Central Nervous System Hypothesismentioning
confidence: 99%
“…High concentrations of insulin receptors have been reported in the cerebral cortex and hippocampus (52), so insulin could have direct effects on activity and cognitive function in the CNS (22). It influences cognitive functions by modulating neurotransmitter release and synaptic plasticity (24). Also, it modulates acetylcholine and norepinephrine levels in brain and influences cognitive function (19,26).…”
Section: Discussionmentioning
confidence: 99%